COMPARISON OF WALL MATERIAL EFFICIENCY BETWEEN LIGHTWEIGHT BRICKS AND RED BRICKS IN RESIDENTIAL CONSTRUCTION - Hutagaol, Kerlima; Samosir, March German; Saripuddin, Imron; Andhy S, Nanang; E, Meliana Nur (Universitas Dharmawangsa Medan, 2026)
Wall work is a crucial part of building construction, impacting the cost and time of a project. The selection of wall materials, such as lightweight bricks and red bricks, is crucial for optimal efficiency. This study aims to compare the efficiency of lightweight brick and red brick wall materials in residential construction, in terms of cost and time.The research method used was a comparative descriptive approach with a case study approach on a 100 m² residential construction project. The data analyzed included material costs, labor costs, and the duration of the wall work for each material. The analysis was conducted by comparing the total cost per square meter and the productivity of the work time in the field.The results of the study showed that the total cost of wall work using red brick was Rp145,000/m², while lightweight brick was Rp175,000/m². However, the implementation time using lightweight brick was shorter, which was around 8–9 days compared to red brick which reached 12–13 days. Thus, red brick was more efficient in terms of cost by 17.14%, while lightweight brick was more efficient in terms of time by 30.77%.In conclusion, the choice of wall material should be tailored to project priorities. If the project emphasizes timeliness, lightweight brick is more recommended. However, if the focus is on cost savings, red brick is a more efficient choice.